Adsorption studies of hazardous malachite green onto treated ginger waste - Ahmad, Rais; Kumar, Rajeev (Journal of Environmental Management, 2010)
Adsorption of malachite green (MG) from aqueous solution onto treated ginger waste (TGW) was investigated by batch and column methods. The effect of various factors such as initial dye concentration, contact time, pH and temperature were studied. The maximum adsorption of MG was observed at pH 9. Langmuir and Freundlich isotherms were employed to describe the MG adsorption equilibrium. The monolayer adsorption capacities were found to be 84.03, 163.9 and 188.6 mg/g at 30, 40 and 50 °C, respectively. The values of thermodynamic parameters like ΔG°, ΔH° and ΔS° indicated that adsorption was spontaneous and endothermic in nature. The pseudo second order kinetic model fitted well in correlation to the experimental results. Reichenberg's equation was employed to determine the mechanism of adsorption. The results indicated that film diffusion was a major mode of adsorption. The breakthrough capacities were also investigated.